Konten Analisis Program Mimbar Agama Islam Di Radio Dsb 93.80 Mhz - Rahmadona Indriana; Abdul Rasyid (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2023)
This article aims to discuss the content analysis of the Islamic Religion Mimbar program on DSB Radio 93.80 MHz. Local radio must also compete with national or private television stations which have very strong networks with capital, excellent quality, and professional personnel. Local exhibitions with religious, social, cultural, tourism, economic and other regional characteristics are of course important for all levels of society. As a result, observing the evolution of radio transmission is of little interest to the general public. Has Radio DSB 98.80 Deli Serdang succeeded in presenting content that can attract listeners to the Islamic pulpit program? The purpose of this research is to examine and analyze the positive things that can be studied from the content of the Islamic Religion Mimbar program. The qualitative research approach used is the In-Dept Interview research methodology, which is a technique or method of searching data with this technique which is carried out in detail to informants in the form of questions or oral conversations. The results of the study show that the content presented by Radio DSB 98.80 Deli Serdang has used a communication strategy. The communication strategy implemented so that the content can be heard by many people is to know the audience or target listeners, compose messages into content scripts, and apply informative, persuasive and educative methods.